The Evaluation of Pharmacy Strategic Plan in Past 2013-2016 and Forecasting of New Vision 2030 at Ministry of Health in Saudi Arabia - Alomi, Yousef Ahmed; Alghamdi, Saeed Jamaan; Abdullah Alattyh, Radi; Abdelsalam Elshenawy, Rasha (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the outcomes of strategic plan implementations in past 2013-2016 and to update the pharmacy strategic plan based on new Saudi vision 2030. Method: It is a cross-sectional follow-up, monitor, and forecasting of General Administration of the pharmaceutical care strategic plan in 2016-2020. The authors review all six strategic plan, seventeen initiatives, and eighty-three projects. The Assessment from the baseline before applying the strategic plan 2013 to 2016 at MOH hospitals and primary care centers. The new updating of a strategic plan based new vision of Ministry of Health and Saudi vision 2030 and correlate with them accordingly. Results: The total project of past strategic plan was 84 projects. The total number of fully implemented projects were at hospital 29 (34.5%) projects, and primary care centers were 19 (22.6%) projects. The total number of some implemented programs at the hospital was 28 ( 33.33%) while at primary care centers were 26 (30.95%) projects. The total number not implemented at hospitals were 25 ( 29.76%) while at primary care centers were 36 ( 42.85%). The total number of new projects added to the new plan was seven, and a total number of deleted projects was one. The total number of projects with new strategic plan vision 2030 were ninety projects. Conclusion: The last pharmacy strategic plan at Ministry of Health organization was beneficial during 2013-2016. Several programs implemented for the first time. That is including but not limited to stewardship of antimicrobial program, pain management program, and medication safety program. The new updating pharmacy strategic plan compatible and support the Ministry of Health and Kingdom of Saudi Arabia new strategic plan with new vision 2030.
Keywords: Pharmacy; Strategic plan; Forecasting; Vision 2030; Ministry of Health; Saudi Arabia